Revitalisasi Rumah Tradisional Gamav Aha: Adaptasi Desain dan Sakralitas dalam Konteks Ritual Katolik di Kawasan Sinai, Papua Selatan - Raubaba, Henry Soleman; Sari, Suzanna Ratih; Wijayanti , Wijayanti; Sardjono, Agung Budi (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
The revitalization of the traditional Gamav Aha house as a sacred space within Catholic ritual practice has become a central issue in the cultural and religious life of the Malind Anim community in the Sinai area of South Papua. The disappearance of Gamav Aha due to modernization has threatened not only the sustainability of tangible heritage but also the collective meaning and cultural identity of the community. This study aimed to analyze the process of revitalizing Gamav Aha as a sacred space through design adaptation, functional transformation, and meaning negotiation within the context of Catholic rituals. A qualitative descriptive method was employed, and fieldwork was conducted in July 2024 across three main villages in the Sinai area: Urumb, Waninggap Nanggo, and Matara. Data were collected through participatory observation, in-depth interviews with traditional, religious, and community leaders, and visual documentation of spaces and ritual activities. The findings showed that revitalization was realized through innovations in physical design, including adjustments in layout, structure, materials, and spatial orientation. The transformation of Gamav Aha from a dwelling into a temporary sacred space, enriched with cultural and religious symbolism, strengthened community identity. These results underscore the importance of adaptive design strategies rooted in local wisdom for the preservation of vernacular architecture and the reinforcement of social cohesion within indigenous communities in the modern era.